Performance measurements of diversity combining technique using multiple antennas for IEEE 802.15.4 wireless personal area networks - Paulino, Issa M.
Zigbee is the technology most practical for wireless personal area networks which require low data rates and low power consumption. With Zigbee devices scattered in indoor environments, i.e. buildings, receive and transmit signals can be reflected from various obstacles resulting in multipath propagation. Bounces on obstacles can introduce phase shifts, time delays, attenuation and distortion. A way to eliminate and turn multipath into a benefit for the system is the use of antenna diversity. Antenna diversity is the use of two or more antennas to improve the quality and reliability of a wireless link. Thus, if one of the antennas is experiencing attenuation, it is likely that another has sufficient signal. The project aims to acquire the performance of a ZigBee receiver with an antenna array of four omni-directional antennas. Fixed ZigBee nodes will be scattered and will transmit data to the receiver which is connected to a PC with running RF Studio that measures the received signal strength (RSSI) and packet error rate (PER) from each test point. Through a series of tests, a characterization of the environment will be acquired. Diversity techniques for the receiver of the network will be implemented to improve power consumption and throughput. An algorithm for switching antennas that will automate antenna diversity and combining depending on the RSSI and PER level at a certain test point will be tested.